2011
DOI: 10.1183/09031936.00026011
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of endurance activity following pulmonary rehabilitation in COPD patients

Abstract: Maintenance of physical activity following pulmonary rehabilitation remains a challenge for patients with chronic obstructive pulmonary disease (COPD). The objectives of this study were to identify patterns of endurance activity after completion of pulmonary rehabilitation and to characterise people who succeed and those who have difficulty maintaining endurance activity.In a longitudinal study embedded within a randomised clinical trial, 206 individuals with COPD underwent a 3-month pulmonary rehabilitation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 46 publications
3
34
1
6
Order By: Relevance
“…Remaining challenges are the limited access to PR programs 52 as well as maintaining initial benefits and their translation into active lifestyles. 48 In this paper we have shared our own views about PR but we clearly encourage the creation of a diversity of programs and intervention to promote an active life style in a larger COPD population. These programs, however small they might be, should be well structured, done by a multidisciplinary team specifically trained in PR and tailored to the patients' needs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Remaining challenges are the limited access to PR programs 52 as well as maintaining initial benefits and their translation into active lifestyles. 48 In this paper we have shared our own views about PR but we clearly encourage the creation of a diversity of programs and intervention to promote an active life style in a larger COPD population. These programs, however small they might be, should be well structured, done by a multidisciplinary team specifically trained in PR and tailored to the patients' needs.…”
Section: Discussionmentioning
confidence: 88%
“…16,19,24,48 Because home-based rehabilitation may be the most convenient, it may appear to be superior to center-based programs in terms of long term adherence to exercise. 49 Thus, patients are encouraged to continue their training by either remaining in a hospital-or community-based program, or by initiating a home-based program.…”
Section: Home-rehabilitation Programmentioning
confidence: 99%
“…Pulmonary rehabilitation and chronic care have received a lot of attention in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In turn, several interesting research abstracts were presented at the 2013 European Respiratory Society Congress, of which many were on the topic of comorbidities [29][30][31][32][33].…”
Section: Rehabilitation and Chronic Carementioning
confidence: 99%
“…These authors have shown that specific arm performance may improve arm capacities, a result still maintained over 6 months. This is particularly important as maintenance of daily activities after rehabilitation is a difficult task for COPD patients [14]. JANUDIS-FERREIRA et al [15] demonstrated that resistance-based arm training improved arm function, strength and exercise capacity although this did not translate into lower dyspnoea during domestic activities.…”
mentioning
confidence: 99%